2005
DOI: 10.1007/s10979-005-5521-x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting deception via strategic disclosure of evidence.

Abstract: Several decades of research has shown that people are poor at detecting deception. This thesis, based on four empirical studies, aimed at exploring human deception detection accuracy in the context of interrogations. In three of the studies, there was a special focus on the presence of evidence in the interrogation, and how strategic use of this evidence affected the statements of the suspects as well as the accuracy of the lie-catchers. In previous research, the fact that there in real-life situations often e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
233
2
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(258 citation statements)
references
References 70 publications
(149 reference statements)
18
233
2
5
Order By: Relevance
“…In some experimental studies that have favoured a 'late' EDM approach (e.g. Hartwig et al, 2005Hartwig et al, , 2006Sorochinski et al, 2014) the methodologies involved either a somewhat simplistic mock offence or (when the task was more complex) 'suspects' having only a short amount of time to create their story. Neither of these two scenarios may have always particular resonance to reallife.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In some experimental studies that have favoured a 'late' EDM approach (e.g. Hartwig et al, 2005Hartwig et al, , 2006Sorochinski et al, 2014) the methodologies involved either a somewhat simplistic mock offence or (when the task was more complex) 'suspects' having only a short amount of time to create their story. Neither of these two scenarios may have always particular resonance to reallife.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have found an association between the revelation of evidence and the gaining of further information (Bull & Leahy-Harland, 2012;Nystedt, Nielsen, & Kleffner, 2011;van der Sleen, 2009), while other (experimental) studies have revealed that certain evidence disclosure strategies have contributed to the rigorous testing of given accounts by mock suspects, and, in turn, the detection of either lies or truth (Dando, Bull, Ormerod, & Sandham, in press;Granhag, Strömwall, Willén, & Hartwig 2012;Hartwig, Granhag, Strömwall, & Kronkvist 2006;Hartwig, Granhag, Strömwall, & Vrij, 2005;Sorochinski et al, 2014). Yet other studies have found that disclosing strong evidence is associated with suspects' confessions (Bull & Soukara, 2010;Cassell & Hayman, 1996;Gudjonsson & Petursson, 1991;Kebbell, Hurren, & Roberts, 2006;Moston, Stephenson, & Williamson, 1992;Sellers & Kebbell, 2009;Soukara et al, 2009;Walsh & Bull, 2012a).…”
Section: Evidence Disclosure In Interviews With Suspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…'Gradual' evidence disclosure involves a phased presentation of information/evidence, provided in a 'drip-feed' effect throughout the interview (Dando & Bull, 2011;Granhag et al, 2012). In contrast, 'late' disclosure relates to the gathering of the whole story from the suspect, and dealing with all potential alibis and the like, before presenting the evidence (see Hartwig et al, 2005;2006, Sorochinski et al, in press). …”
Section: Evidence Disclosure Strategiesmentioning
confidence: 99%